Nonverbal content and trust: An experiment on digital communication - Zakaria Babutsidze; Nobuyuki Hanaki; Adam Zylbersztejn (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We experimentally study the effect of the mode of digital communication on the emergence of trust in a principal-agent relationship. We consider three modes of communication that differ in the capacity to transmit nonverbal content: plain text, audio, and video. Communication is pre-play, one-way, and unrestricted, but its verbal content is homogenized across treatments. Overall, both audio and video messages have a positive (and similar) effect on trust as compared to plain text; however, the magnitude of these effects depends on the verbal content of agent's message (promise to act trustworthily vs. no such promise). In all conditions, we observe a positive effect of the agent's promise on the principal's trust. We also report that trust in female principals is sensitive to the availability of nonverbal cues about their partners.
Keywords: C72; D83; 330; Digital communication; Trust; Hidden action; Nonverbal content; Principal-agentrelationship; Promises